2009
DOI: 10.15835/nsb113459
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Zea mays as Influenced by NPK fertilizer Application

Abstract: Field trials were made to estimate the effect of NPK 15:15:15 fertilizer on the growth and yield of maize were conducted over a two year period. NPK fertilizer applications significantly increase plant height, stem girth, number of leaves, leaf area, leaf area index, dry matter accumulation and yield. The optimum level of NPK 15:15:15 fertilizer for successful production of maize grains was 400 (60 kg N + 27.16 kg P + 49.80 kg K) kg / ha compound fertilizer based on the fact that it had the greatest dry cob yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 4 publications
3
14
0
1
Order By: Relevance
“…This is significantly higher than average fertilizer used by rainforest (153.56 kg/ha) and montane savanna (125.75 kg/ha) respectively. The yearly average of the sample was about 272.6 kg/ha which is lower than the recommended usage of 400 kg/ha application level for effective optimum growth and yield of maize (Law-Ogbomo, 2009). The result also shows that maize farmers in the guinea savanna used an average 12.6litres/ha of pesticides which is significantly higher than average pesticides used by montane savanna (2.98 lt/ha) and rainforest (2.87 lt/ha) respectively.…”
Section: Farm Characteristicsmentioning
confidence: 72%
“…This is significantly higher than average fertilizer used by rainforest (153.56 kg/ha) and montane savanna (125.75 kg/ha) respectively. The yearly average of the sample was about 272.6 kg/ha which is lower than the recommended usage of 400 kg/ha application level for effective optimum growth and yield of maize (Law-Ogbomo, 2009). The result also shows that maize farmers in the guinea savanna used an average 12.6litres/ha of pesticides which is significantly higher than average pesticides used by montane savanna (2.98 lt/ha) and rainforest (2.87 lt/ha) respectively.…”
Section: Farm Characteristicsmentioning
confidence: 72%
“…, respectively. The corresponding values for soybean plants were 31.83 and 45.50 cm. In all cases the differences among the 3 levels of bulk density were significant (P = .05).…”
Section: Plant Heightmentioning
confidence: 91%
“…This observation is in line with [26] who reported that nutrient from mineral fertilizers enhance the establishment of crops prior to their influence on soil properties. Although maize is a short term crop, it has a strong nutrient exhaustive effect in soils [27]. This incidence might have resulted in the low chemical properties of the soil among experimental plots despite their recommended and higher application rate.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%